2017
DOI: 10.1093/femsec/fix099
|View full text |Cite
|
Sign up to set email alerts
|

Signatures in the gut microbiota of Japanese infants who developed food allergies in early childhood

Abstract: Bacterial colonization in infancy is considered crucial for the development of the immune system. Recently, there has been a drastic increase in childhood allergies in Japan. Therefore, we conducted a prospective study with 56 infants on the relationship between gut microbiota in the first year of life and the development of allergies during the first 3 years. In the lactation period, organic acid producers such as Leuconostoc, Weissella and Veillonella tended to be underrepresented in subjects who developed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 46 publications
3
32
0
8
Order By: Relevance
“…Both PCRs were performed as described previously. 8 Amplicons from the second PCR were purified using FastGene Gel/PCR Extraction Kit (Nippon Genetics Co., Ltd.), and the DNA concentrations were measured using PicoGreen® ds DNA Assay Kit (Life Technologies) in a Tecan M200 (excitation at 480 nm and emission at 520 nm). A pool of equal amounts (200 ng) of amplicons from each sample was purified by electrophoresis in 2% (w/v) agarose gel, followed by extraction from the gel using FastGene Gel/PCR Extraction Kit.…”
Section: S Rrna Gene Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…Both PCRs were performed as described previously. 8 Amplicons from the second PCR were purified using FastGene Gel/PCR Extraction Kit (Nippon Genetics Co., Ltd.), and the DNA concentrations were measured using PicoGreen® ds DNA Assay Kit (Life Technologies) in a Tecan M200 (excitation at 480 nm and emission at 520 nm). A pool of equal amounts (200 ng) of amplicons from each sample was purified by electrophoresis in 2% (w/v) agarose gel, followed by extraction from the gel using FastGene Gel/PCR Extraction Kit.…”
Section: S Rrna Gene Sequencingmentioning
confidence: 99%
“…1,[4][5][6] The developing microbiota has a great impact on infant health and subsequent host physiology, notably through the development of the digestive tract, immune system, and metabolic homeostasis. 6,7 Therefore, failure in gut microbiota development may lead to diseases such as food allergies, 8,9 asthma, 10 atopic dermatitis, 11 and childhood obesity. 12,13 Bile acids (BAs) constitute the primary component of bile.…”
Section: Introductionmentioning
confidence: 99%
“…The amplified products were then used as templates in a second PCR for further amplification using barcode-tagged primers. Both PCRs were performed as described previously 39 . PCR products were pooled and combined in equimolar amounts for sequencing using the Illumina MiSeq platform, generating 300 bp paired-end reads.…”
Section: Methodsmentioning
confidence: 99%
“…Compared with germ-free controls, the mice colonized with Clostridium clusters showed reduced levels of peanut-specific and total IgE and no drop in rectal temperature on allergen challenge. 27 Although many studies in murine models have found that taxa from Clostridia confer an overall protective effect on the host, their association with atopic risk has been more variable in human studies 5,8,9,11,28,29…”
Section: Immune Maturation and Tolerancementioning
confidence: 99%